Comparative study of abnormalities of central nervous system in children and adults autopsied after bone marrow transplantation Estudo comparativo das alterações no sistema nervoso central de crianças e adultos autopsiados após transplante de medula óssea - Paulo R. Benites Filho; Luis G. M. Pinto de Almeida; José Zanis Neto; Ricardo Pasquini; Luiz F. Bleggi-Torres (Sociedade Brasileira de Patologia Clínica, 2007)
BACKGROUND: We compare neuropathological abnormalities in children and adults after bone marrow transplantation (BMT) by means of autopsy in the Department of Medical Pathology, Universidade Federal do Paraná (UFPR), Brazil. METHODS: Autopsy reports of 180 patients were reviewed. They were divided in two groups: patients under 15 years old and those 15 or older. Age, gender, clinical diagnosis at time of BMT, survival time, neuropathological abnormalities and cause of death were analyzed. RESULTS: In children (26.6% of total) and in the adult group (73.4% of total), the main clinical diagnoses prior to BMT were, respectively, severe aplastic anemia (31.2%) and chronic myeloid leukemia (36.3%). The mean survival time for children was 102.6 days and for adults, 185.9 days after BMT. Brain lesions were considered cause of death in 20.8% of pediatric cases and 11.3% of the adult group. Neuropathological abnormalities were morphologically similar in children and adults, with the following respectively prevalence: cerebrovascular diseases in 58.3 and 56% (p = 0.8655), neurotoxoplasmosis in 6.2% and 3% (p = 0.3856) and infections in 27 and 25.7% (p = 0.8489). CONCLUSIONS: The pediatric patients had shorter survival than adults, with increasing prevalence of neurotoxoplasmosis, and brain lesions were considered cause of death in twice as many as compared to adult patients. INTRODUÇÃO: Foram comparadas as anormalidades encontradas no sistema nervoso central de adultos e crianças submetidos à autópsia após transplante de medula óssea (TMO) no Departamento de Patologia Médica da Universidade Federal do Paraná (UFPR). MÉTODOS: Relatórios das autópsias de 180 pacientes foram revistos. Foram considerados crianças os pacientes abaixo de 15 anos; adultos, aqueles com 15 ou mais. A idade, o sexo, o diagnóstico clínico na época do TMO, o tempo de sobrevivência, as anormalidades neuropatológicas e a causa da morte foram analisados. RESULTADOS: Nas crianças (26,6% do total) e nos adultos (73,4% do total) o principal diagnóstico clínico prévio ao TMO foi, respectivamente, anemia aplásica severa (31,2%) e leucemia mielóide crônica (36,3%). O tempo médio de sobrevivência pós-TMO para crianças foi de 102,6 dias; para os adultos, 185,9. Lesões cerebrais foram consideradas causa de morte em 20,8% dos casos pediátricos e 11,3% do grupo adulto. As anormalidades neuropatológicas foram morfologicamente similares nas crianças e nos adultos e apresentaram, respectivamente, as seguintes prevalências: doenças cerebrovasculares em 58,3% e 56% (p = 0,8655), neurotoxoplasmose em 6,2% e 3% (p = 0,3856) e infecções em 27 e em 25,7% (p = 0,8489). CONCLUSÕES: As crianças tiveram sobrevida menor, maior número de casos de neurotoxoplasmose e duas vezes mais lesões graves do sistema nervoso central que o grupo adulto.